SUPPLY CHAIN OF SELECTED FRUITS IN HYDERABAD AND SOURCES OF FINANCE TO THE SUPPLY CHAIN PARTNERS - SEEMA, ATIFA TAMKEE, P. RADHIKA and (The Journal of Research, PJTSAU, 2019)
The flow of funds to and among the various links within supply chain comprises what is known as supply chain finance. Stated another way, it is any or all of the financial services, flowing to and/or through a value chain to address the needs and constraints of those involved in that chain to access finance. (Miller and Jones, 2010).